RELATIONSHIP OBESITY WITH THE MENSTRUAL CYCLE ON STUDENTS SMAN 2 BANDAR LAMPUNG - Rehana, Intan; Berawi, Khairunissa; Susianti, Susianti; Muhartono, Muhartono (Majority, 2015)
One of the typical maturity of a woman is menstruating. However, the variation of the menstrual cycle and menstrual disorders often occur. Irregular menstrual cycles have implications for women's health. There are many things that affect the menstrual cycle, including nutritional status. Women who are obese are more prone to disruption the menstrual cycle due to the influence of Adypocyte -derived hormone leptin from body fat. This type of analytic research with cross sectional approach that aims to the relationship of obesity with the menstrual cycle. The number of samples in this study amounted to 107 people with a sampling technique with simple random sampling method. Data on menstrual cycle obtained from interviews while body mass index obtained from direct measurements. The result showed that the average weight of the sample was 57.42 kg with a mean height of the sample was equal to 158.40 cm, while the mean body mass index of the sample was equal to 22.40. Fischer test results obtained significant association between obesity and the menstrual cycle in students SMA N 2 Bandar Lampung with p = 0.032 ( p < 0.05 ). Key word: Leptin, menstrual cycle, nutritional status, obesity